Modeling of multicomponent and multitemperature adsorption equilibria of water vapor and organic compounds on activated carbons - Józef Nastaj; Konrad Witkiewicz; Małgorzata Chybowska (Adsorption Science & Technology)
Adsorption equilibria of the pure component and binary gaseous mixtures of water vapor and organic compound (toluene or n-butanol) on two selected activated carbons: Sorbonorit 4 and BPL 4×6 were studied. A mathematical model of the adsorption equilibrium for binary systems with the virial mixture coefficients has been developed based on the two-dimensional virial equation of state. In the modeling, the experimental adsorption equilibrium data of pure components were correlated by the Toth isotherm for organic compounds, and Talu–Meunier or Qi–LeVan models for water vapor. Additionally, multitemperature isotherms for pure component were calculated to determine virial mixture coefficient of the two-dimensional virial equation of state depending on temperature. Adsorption isotherms determined for two-component systems were compared with multicomponent adsorption equilibrium data obtained experimentally by a dynamic method at relative humidities of the carrier gas set at 25, 50, 75, and 90%. A fairly good agreement between simulations and experimental results was obtained using expansion of the two-dimensional virial equation of state through D terms.